La pratique des langues autochtones au Mexique, xvie-xxie siècles - Patrick Johansson Keraudren (La Bretagne Linguistique, 2018)
This paper, although ostensibly out of context geographically speaking with the theme of the La Bretagne linguistique colloquium at which it was presented, was nevertheless situated within the same thematic framework from the point of view of some of the diachronic and synchronic aspects that have marked the evolution in the use of vernacular languages throughout history and their relationship to the so-called national languages. There are probable similarities in this respect between some of the sociolinguistic relationships maintained over the centuries between Breton and first Latin then French and between Nahuatl and Spanish. This paper begins by defining the polysynthetic nature of the Aztecs’ language and then considers the specific modalities of language contact between Nahuatl and Spanish throughout history. It looks at the neologisms created in both languages, the religious leaders’ exploitation of the particular discursiveness of the Nahuatl language, the stigma attached to speaking Nahuatl after Mexico’s Independence and the prolific interpenetration of Nahuatl and the Iberian language in the Spanish spoken in Mexico today.